Extractive bioconversion of cyclodextrins by Bacillus cereus cyclodextrin glycosyltransferase in aqueous two-phase system - Ng, Hui Suan; Ooi, Chien Wei; Mokhtar, Mohd Noriznan; Show, Pau Loke; Ariff, Arbakariya; Tan, Joo Shun; Ng, Eng Poh; Ling, Tau Chuan (Elsevier, 2013)
An extractive bioconversion with Bacillus cereus cyclodextrin glycosyltransferase (CGTase, EC 2.4.1.19) in aqueous two-phase system (ATPS) was investigated for the synthesis and recovery of cyclodextrins (CDs). Optimum condition for the extractive bioconversion of CDs was achieved in ATPS consisted of 7.7% (w/w) polyethylene glycol (PEG) 20,000 and 10.3% (w/w) dextran T500 with volume ratio (VR) of 4.0. Enzymatic conversion of starch occurred mainly in dextran-rich bottom phase whereas the product, CDs was transferred to top phase and a higher partition coefficient of CDs was achieved. Repetitive batch of CDs synthesis was employed by replenishment of the top phase components and addition of starch every 8 h. An average total CDs concentration of 13.7 mg/mL, (4.77 mg/mLα-CD, 5.02 mg/mLβ-CD and 3.91 mg/mLγ-CD) was recovered in the top phase of PEG 20,000/dextran T500 ATPS. This study showed the effectiveness of ATPS application in extractive bioconversion of CDs synthesis with B. cereus CGTase.